Walrus Island – A pivotal place for High Arctic Palaeo-Eskimo societies in Northeast Greenland - Sørensen, Mikkel (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2012)
AbstractIn this article, the Palaeo-Eskimo ruin features of the Walrus Island site are presented and analysed. The Walrus Island site was investigated in 2008 and more than 2,000 stone features were recorded, of which 445 were the remains of dwellings attributed to Palaeo-Eskimo occupations. These ruins are described as “mid-passages,” “tent rings,” “clearings,” and “pavements.” They are associated with lithic artefacts that attest to the presence of all the previously identified Palaeo-Eskimo cultures of Northeast Greenland, i.e., Independence I, Saqqaq, and Greenlandic Dorset. Based on the ruins’ location near sloping terrain and lack of peripheral stones, it is argued that the Greenlandic Dorset people built snow houses on the site. Walrus Island has the second largest known Palaeo-Eskimo site in Northeast Greenland, the largest one being the Kap Skt. Jacques site on the island Île-de-France, which has 548 features. Both sites, and four other large or potentially very large sites, have in common a shore location on the Northeast Greenland coast near polynyas. These large sites were of pivotal importance for the Palaeo-Eskimos of Northeast Greenland and may help us understand their way of life in the extreme High Arctic.